Depression and materialistic values : relationship between materialistic values and symptoms of depression in Chinese adolescents. - Tan, Li Hui. (2009)
The current study utilized a multi-wave longitudinal design and examined whether using adaptive/maladaptive coping strategies would mediate the relationship between materialistic values and depression. Whether a lack of perceived social support would affect the association of the meditational pathways was also further examined. Initially, participants completed measures assessing their level of materialism, coping strategies, lack of perceived social support, and depression. During the follow-up, participants completed measure assessing only depression. Results of multilevel modeling indicated that both adaptive and maladaptive coping mediated the relationship between materialistic values and depression. Also, while the lack of perceived social support significantly moderated the relationship between adaptive coping and depression, it did not significantly moderate the relationship between maladaptive coping and depression.